2010
DOI: 10.1063/1.3365531
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and magnetocaloric effects in antiferromagnetic ErTiSi

Abstract: Magnetic properties and magnetocaloric effects ͑MCEs͒ of the antiferromagnetic ͑AFM͒ ErTiSi compound with a Néel temperature T N = 46 K are studied by magnetization measurements. Two successive magnetic transitions in the thermomagnetic M-T curves, an AFM-AFM transition followed by an AFM-paramagnetic transition with increasing temperature, are observed. ErTiSi undergoes a field-induced metamagnetic transition from AFM to FM state below T N. A sign change in MCE with increasing temperature or magnetic field in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
2
Order By: Relevance
“…33 While very similar concerns about the magnetic order parameters in antiferromagnetics were raised by Gschneidner et al, 44 treating the measured magnetization as the primary order parameter is frequently used in the magnetocaloric community. [45][46][47][48][49][50][51][52] It seems that the indirect method might still yield reasonable estimations about direct measurement results. For instance, it was reported that the direct measurement results in FeRh compounds can be well reproduced by the indirect method based on the magnetization measurements.…”
Section: Negative Electrocaloric Effect In Antiferroelectricsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 While very similar concerns about the magnetic order parameters in antiferromagnetics were raised by Gschneidner et al, 44 treating the measured magnetization as the primary order parameter is frequently used in the magnetocaloric community. [45][46][47][48][49][50][51][52] It seems that the indirect method might still yield reasonable estimations about direct measurement results. For instance, it was reported that the direct measurement results in FeRh compounds can be well reproduced by the indirect method based on the magnetization measurements.…”
Section: Negative Electrocaloric Effect In Antiferroelectricsmentioning
confidence: 99%
“…[48][49][50][51] To simplify, in Figure 6, we do not consider any specific information such as the material and the direction of fields but focus on the general physical behavior of an antiferroic system. The magnetocaloric or electrocaloric entropy change DS with a positive sign at lower temperatures ((T C ) (1) first experiences an increase in its magnitude (becoming more positive) with magnetic or electric field increasing; (2) jDSj then decreases when a critical magnetic or electric field is reached; and (3) DS changes its sign from positive to negative, which indicates that the nature of magnetocaloric or electrocaloric effect changes from negative type to positive type (also see positive electrocaloric entropy change in Figures 2(e) and 2(f)).…”
Section: Negative Electrocaloric Effect In Antiferroelectricsmentioning
confidence: 99%
“…三元低温磁制冷材料按结构分主要有ZrNiAl型 [50][51][52][53][54][55][56][57][58] 、 MgZn 2 型 [59] 、CeFeSi型 [60] 、ThCr 2 Si 2 型 [61] 、AlB 2 型 [62,63] 等.…”
Section: 三元稀土金属间化合物unclassified
“…Ho, Er, Tm)稀土金属间化合物的相变温度从Gd的50 K 降低到Tm的2 K [59][60][61][62][63][64] . GdCuAl和TbCuAl属于反铁磁材 料 [52,53] , 而R=Dy, Ho, Er, Tm属于铁磁性材料 [54][55][56] .…”
Section: 三元稀土金属间化合物unclassified